A cell wall-localized glycine-rich protein of dodder acts as pathogen-associated molecular pattern - Slaby, Peter; Körner, Max; Albert, Markus (Communitative and Integrative Biology, 2021)
Cuscuta reflexa (giant dodder) is an obligate stem holoparasite withdrawing water, nutrients, and carbohydrates from its hosts. For a broad spectrum of host plants, C. reflexa usually stays unrecognized. The cultivated tomato Solanum lycopersicum, as one notable exception, possesses a leucine-rich repeat receptor protein (LRR-RP), Cuscuta receptor 1 (CuRe1), which enables tomato to recognize C. reflexa as a dangerous parasitic invader and to respond with plant immune responses. During the infection process, a glycine-rich protein (GRP) is freed from C. reflexa and gets detected by CuRe1. Here, we focus on the subcellular localization of the GRP within plant cell walls using a fluorescence based co-localization.
Created from Fastlane, Scopus look-up
Keywords: CuRe1; Cuscuta reflexa; Glycine-rich protein; GRP; parasitic plants

Quinones shuffling the CARDs - Körner, Max; Slaby, Peter; Albert, Markus (Nature Plants, 2020)
CRIS-Team Scopus Importer:2020-09-11

The tomato receptor CuRe1 senses a cell wall protein to identify Cuscuta as a pathogen - Hegenauer, Volker; Slaby, Peter; Körner, Max; Bruckmueller, Julien-Alexander; Burggraf, Ronja; Albert, Isabell; Kaiser, Bettina; Loeffelhardt, Birgit; Droste-Borel, Irina; Sklenar, Jan; Menke, Frank L. H.; Macek, Boris; et al. (Nature Communications, 2020)
Parasitic plants of the genus Cuscuta penetrate shoots of host plants with haustoria and build a connection to the host vasculature to exhaust water, solutes and carbohydrates. Such infections usually stay unrecognized by the host and lead to harmful host plant damage. Here, we show a molecular mechanism of how plants can sense parasitic Cuscuta. We isolated an 11 kDa protein of the parasite cell wall and identified it as a glycine-rich protein (GRP). This GRP, as well as its minimal peptide epitope Crip21, serve as a pathogen-associated molecular pattern and specifically bind and activate a membrane-bound immune receptor of tomato, the Cuscuta Receptor 1 (CuRe1), leading to defense responses in resistant hosts. These findings provide the initial steps to understand the resistance mechanisms against parasitic plants and further offer great potential for protecting crops by engineering resistance against parasitic plants.
Created from Fastlane, Scopus look-up